if you help me in this question I'll mark you as a brainliest
Attachments:
![](https://hi-static.z-dn.net/files/d58/0dd5c4ec845058d949f5273c32b77671.jpg)
Answers
Answered by
2
Answer:
Step-by-step explanation:
Attachments:
![](https://hi-static.z-dn.net/files/de7/87be6bc83e51c748e75c372551f07860.jpg)
Answered by
1
sin(A+36)=cosA ----- 1
cosA=sin(90-A) ----- 2
From equation 1 and 2 we get,
sin(A+36)=sin(90-A)
A+36=90-A
2A=54
A=27
Hope this helps you!
cosA=sin(90-A) ----- 2
From equation 1 and 2 we get,
sin(A+36)=sin(90-A)
A+36=90-A
2A=54
A=27
Hope this helps you!
pratyanshi:
plz mark me as brainliest
Similar questions